A Hybrid‐Type CVD System for Graphene Growth1. Issue 7 (September 2015) - Skoblin, Grigory; Lindvall, Niclas; Sun, Jie; Yurgens, August
Abstract : A cold‐wall CVD system for graphene growth on metal foils is converted to an effectively hot‐wall one by merely adding another heater, sandwiching the foil in between the heaters. This simple design demonstrates both an improved temperature uniformity characteristic for hot‐wall systems, and a high responsivity distinctive for cold‐wall ones. This beneficial combination allows for a much better control of graphene growth kinetics. Abstract : An effectively hot‐wall system for graphene growth is made from a cold‐wall one by encapsulating the metal foil in between two heaters. This simple conversion demonstrates improved temperature control and high temperature ramping rate. It also allows reaching lower nucleation density and provides better control of growth kinetics.